A Newly Discovered Latin Prose Brut Manuscript at Downside Abbey. Issue 4 (October 2019) - Bateman, Mary
This article provides the first detailed study of a manuscript held in the archives of Downside Abbey in Stratton-on-the-Fosse, Somerset, United Kingdom. The manuscript, Downside 78291 (henceforth F ), contains a Latin prose chronicle that has not previously been described or identified. The present article demonstrates that it is a copy of the chronicle known as the Latin Prose Brut. After a codicological and paleographical study of the manuscript itself, I contextualise this witness within the wider Latin Prose Brut tradition and make some suggestions about the kind of person who might have contributed to the unique variants presented in this version. These variants evince a pro-Lancastrian bias common to many Latin Prose Bruts of the 15th century; but there is also evidence of an author keen to emphasise England's historic victories against France.